2022
DOI: 10.3389/fpls.2022.917770
|View full text |Cite
|
Sign up to set email alerts
|

Differential Gene Expression and Withanolides Biosynthesis During in vitro and ex vitro Growth of Withania somnifera (L.) Dunal

Abstract: Ashwagandha (Withania somnifera L. Dunal) is a medicinally important plant with withanolides as its major bioactive compounds, abundant in the roots and leaves. We examined the influence of plant growth regulators (PGRs) on direct organogenesis, adventitious root development, withanolide biosynthetic pathway gene expression, withanolide contents, and metabolites during vegetative and reproductive growth phases under in vitro and ex vitro conditions. The highest shooting responses were observed with 6-benzylami… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
4
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 11 publications
(4 citation statements)
references
References 70 publications
0
4
0
Order By: Relevance
“…On the other hand, out of four auxins, which are indole-3-acetic acid, indole-3-propionic acid, indole-3-butyric acid, and 1-naphthylacetic acid, treatment with indole-3-butyric acid resulted in a high rooting rate and beneficial root morphology [ 43 ]. Additionally, 1.5 mg/L indole-3-butyric acid exhibited the highest rooting responses and 1.0 mg/L indole-3-butyric acid improved fruit yield and biomass [ 44 ]. In this study, auxin-metabolism-related proteins were identified with the irradiation of millimeter waves; and the application of auxin improved wheat growth under flooding conditions although its growth was suppressed by flooding ( Figure 8 ).…”
Section: Discussionmentioning
confidence: 99%
“…On the other hand, out of four auxins, which are indole-3-acetic acid, indole-3-propionic acid, indole-3-butyric acid, and 1-naphthylacetic acid, treatment with indole-3-butyric acid resulted in a high rooting rate and beneficial root morphology [ 43 ]. Additionally, 1.5 mg/L indole-3-butyric acid exhibited the highest rooting responses and 1.0 mg/L indole-3-butyric acid improved fruit yield and biomass [ 44 ]. In this study, auxin-metabolism-related proteins were identified with the irradiation of millimeter waves; and the application of auxin improved wheat growth under flooding conditions although its growth was suppressed by flooding ( Figure 8 ).…”
Section: Discussionmentioning
confidence: 99%
“…Moringa gum is used to relieve headache pain (Anwar et al, 2007;Leone et al, 2015;Matic et al, 2018;Mohamed et al, 2021). Besides, previous studies discovered that Moringa and usually its ethanolic extracts have anticancer properties against liver cancer and colorectal cancer, this anticancer property is related to the bioactive components hexadecanoicacidethyl ester, isopropyl isothiocyanate and D-allose that are found in the extract (Brilhante et al, 2017;Tiloke et al, 2018). It also has a role in inhibiting pancreatic cancer by targeting the cell cycle leading to the accumulation of cells in the G1 phase, also it regulates the NF-Kβ pathway by its downregulation (Tiloke et al, 2018).…”
Section: Medical Usesmentioning
confidence: 99%
“…Withania has antioxidant activities and enhances immunity and the defense system against diseases, also it can decrease stress levels (Mukherjee et al, 2021). Recent studies have reported the role of Withania in managing the symptoms of COVID-19 as it disrupts the protein's spike electrostatic interaction (Prajapati et al, 2022;Thorat et al, 2022).…”
Section: Medicinal Uses Of Withaniamentioning
confidence: 99%
“…These factors negatively affect plant growth and development at the physiological, biochemical, and molecular level, potentially reducing secondary metabolite production (Selmar 2008). Recently, Thorat et al (2023) showed the metabolic and physio-biochemical adjustments which subsequently facilitate the enhanced withanolide contents in shoot and roots of W. somnifera under saline conditions. In W. somnifera, salt stress has been shown to reduce seed germination, plant growth and chlorophyll content as well as induce drastic changes in antioxidant metabolism.…”
Section: Introductionmentioning
confidence: 99%